Cost of management in epistaxis admission: Impact of patient and hospital characteristics. (7th July 2015) - Goljo, Erden; Dang, Rajan; Iloreta, Alfred M.; Govindaraj, Satish
Abstract : Objectives/Hypothesis: To investigate patient and hospital characteristics associated with increased cost and length of stay in the inpatient management of epistaxis. Study Design: Retrospective cross‐sectional study of the 2008 to 2012 National (Nationwide) Inpatient Sample. Methods: Patient and hospital characteristics of epistaxis admissions were analyzed. Multiple linear regression analysis was used to ascertain variables associated with increased cost and length of hospital stay. Variables significantly associated with high cost were further analyzed to determine the contribution of operative intervention and total procedures to cost. Results: A total of 16, 828 patients with an admitting diagnosis of epistaxis were identified. The average age was 67.5; 52.3% of the patients were male; 73.3% of the patients were Caucasian; and 70.7% of the hospital stays were government funded. The average length of stay was 3.24 days, and average hospitalization cost was $6, 925. Longer length of stay was associated with black race, alcohol abuse, sinonasal disease, renal disease, Medicaid, and care at a northeastern U.S. hospital. Increased hospitalization costs of > $1, 000 were associated with Asian/Pacific Islander race; sinonasal disease; renal disease; top income quartile; and care at urban teaching, northeastern, and western hospitals in the United States. High costs were predicted by procedural intervention in patients with comorbid alcohol abuse, sinonasal disease, renal disease, patients with private insurance, and patients managed at large hospitals. Conclusion: Although hospitalization costs are complex and multifactorial, we were able to identify patient and hospital characteristics associated with high costs in the management of epistaxis. Early identification and intervention, combined with implementation of targeted hospital management protocols, may improve outcomes and reduce financial burden. Level of Evidence: 2C. Laryngoscope, 125:2642–2647, 2015